Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja dan Motivasi Kerja Karyawan PT. Berau Karya Indah Surabaya - Hafid Kholidi Hadi (Universitas Negeri Surabaya, 2018)
Today the world a lot of very rapid progress in all aspects of life. Along with this progress, the increasingly felt need for a strong human resources and quality are able to face changes. Limited liability company or PT is a type of profit-oriented business / profit. PT. Berau Karya Indah is a new company in the industrial processing of raw materials which are trying to develop production. This study aims to discuss and analyze the influence of transformational leadership style on performance and motivation of employees of PT. Berau Karya Indah Surabaya. The population used in this study is all that amount company employees 340 people. The sample size in this study 172 respondents using simple random sampling technique. Statistical analysis methods used is structural equationmodeling(SEM). Results this study mention that 1) there is significant relationship between transformational leadership style (X) on the performance of employees (Y1), 2) transformational leadership has significant implications for employee motivation(Y2)